Electrocatalysts: In Situ Electrochemical Activation of Atomic Layer Deposition Coated MoS2 Basal Planes for Efficient Hydrogen Evolution Reaction (Adv. Funct. Mater. 34/2017). (11th September 2017) - Kim, Youngmin; Jackson, David H. K.; Lee, Daewon; Choi, Min; Kim, Tae‐Wan; Jeong, Soon‐Yong; Chae, Ho‐Jeong; Kim, Hyun Woo; Park, Noejung; Chang, Hyunju; Kuech, Thomas F.; Kim, Hyung Ju
Abstract : A novel and effective method to activate the catalytically‐inert basal plane of MoS2 for the hydrogen evolution reaction (HER) is reported by Thomas F. Kuech, Hyung Ju Kim, and co‐workers in article number1701825 . The basal‐plane‐activated MoS2 catalysts, prepared by combining the atomic layer deposition technique and an in situ electrochemical activation process, significantly improve the HER performance.